Theoretical Calculations and Molecular Docking Analysis of 4-(2-(4-Bromophenyl)Hydrazineylidene)-3,5-Diphenyl-4H-Pyrazole Molecule - Gören, Kenan; Bağlan, Mehmet; Tahiroğlu, Veysel; Yildiko, Umit (My University, 2024)
The molecular structure of 4-(2-(4-bromophenyl)hydrazineylidene)-3,5-diphenyl-4h-pyrazole (BHDH) molecule, which is a pyrazole derivative, was investigated theoretically using the Gaussian 09 program according to the Moller-Plesset (MP2) method. The MP2 method was optimized for these theoretical calculations using DGDZVP and 6-311G(d,p) basis sets. By taking geometric structures, Highest-Energy Molecular Orbital (HOMO) and Lowest-Energy Molecular Orbital (LUMO) analysis, Mulliken Atomic Charges, Molecular Electrostatic Potential (MEPS), Nonlinear Optical (NLO) features, and Natural Bond Orbital (NBO) images of the molecule from this optimized structure were analyzed. In the continuation of the study, Absorbed, Distributed, Metabolized, and Excreted (ADME) analysis was performed to evaluate the BHDH molecule as a drug. Many possible drugs for treating various medical diseases have taken their place in the world market. Drug interactions involve combinations with drugs or other substances that change the effect of a drug on the body. Molecular docking analysis of BHDH molecule on obesity disease was performed with acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. The highest binding energies and binding conformations between ligands and enzymes were predicted.
Keywords: BChE; NBO; molecular docking; AChE; ADME